2019
DOI: 10.1017/s002531541900081x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of shrimpPleoticus muelleriin an upwelling region and new implications for latitudinal gradient theories

Abstract: The population dynamics of shrimp Pleoticus muelleri was used as a model to verify if the trend of continuous reproduction periodicity, shorter body size and longevity, and early sexual maturity found in tropical regions is corroborated in upwelling regions. Shrimps were sampled in a region under the influence of upwelling (northern coast of Rio de Janeiro State, Brazil). Characteristics of bottom water were registered, and shrimps were measured (carapace length – CL) and classified by sex and gonadal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…As indicated in the present study and corroborated by results found by Davanso et al (2017) for the same taxon, shrimp in this region reach larger sizes, grow slower, and live longer than those from other regions studied, highlighting subtropical/temperate characteristics in Macaé. Similar results have been reported for Pleoticus muelleri (Spence Bate, 1888) (Sancinetti et al, 2019), Artemesia longinaris Spence Bate, 1888 (Carvalho‐Batista, Pantaleão, et al, 2019), and Exhippolysmata oplophoroides (Holthuis, 1948) (Pescinelli et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As indicated in the present study and corroborated by results found by Davanso et al (2017) for the same taxon, shrimp in this region reach larger sizes, grow slower, and live longer than those from other regions studied, highlighting subtropical/temperate characteristics in Macaé. Similar results have been reported for Pleoticus muelleri (Spence Bate, 1888) (Sancinetti et al, 2019), Artemesia longinaris Spence Bate, 1888 (Carvalho‐Batista, Pantaleão, et al, 2019), and Exhippolysmata oplophoroides (Holthuis, 1948) (Pescinelli et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Also, the SBB is influenced by three distinct water masses: Coastal Water (CW), Tropical Water (TW), and South Atlantic Central Water (SACW) (Silveira et al, 2000; Valentin et al, 1987). TW carries warm and nutrient‐poor water, while SACW carries colder and nutrient‐rich water (Sancinetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2014) and Costa et al (2016) evaluated how bottom water temperature variations modulate the diversity of shrimp (Penaeoidea and Caridea) and Decapoda assemblages, respectively. Sancinetti et al (2014) and Sancinetti et al (2019) evaluated the abundance and distribution of Artemesia longinaris Spence Bate, 1888 and Pleoticus muelleri (Spence Bate, 1888) throughout a depth gradient (5-45 m). Herrera et al (2017) pointed out that the physical and chemical features of the SACW contributed to an increase in abundance of Exhippolysmata oplophoroides (Holthuis, 1948) and a decrease of Nematopalaemon schmitti (Holthuis, 1950).…”
mentioning
confidence: 99%